Scientific activities in and about Greenland: An analysis of actors, activities, and collaboration in Greenlandic research - Krogh Graversen, Ebbe; Pedersen, Asger Dalsgaard (CFA Scientific Reports, 2018)
This report presents the results of an investigation and analysis of opportunities, strengths and challenges of scientific activities involving Greenland as a research area or research object relative to other Arctic areas.